How to HEEAL: A Patient and Peer-Centric Simulation Curriculum for Medical Error Disclosure - Lauren Falvo; Anna Bona; Melanie Heniff; Dylan Cooper; Malia Moore; Devin Doos; Elisa Sarmiento; Cherri Hobgood; Rami Ahmed (Association of American Medical Colleges, 2024)
Introduction Medical errors are an unfortunate certainty with emotional and psychological consequences for patients and health care providers. No standardized medical curriculum on how to disclose medical errors to patients or peers exists. The novel HEEAL (honesty/empathy/education/apology-awareness/lessen chance for future errors) curriculum addresses this gap in medical education through a multimodality workshop. Methods This 6-hour, two-part curriculum incorporated didactic and standardized patient (SP) simulation education with rapid cycle deliberate practice (RCDP). The morning focused on provider-patient error disclosure; the afternoon applied the same principles to provider-provider (peer) discussion. Summative simulations with SPs evaluated learners' skill baseline and improvement. Formative simulations run by expert simulation educators used RCDP to provide real-time feedback and opportunities for adjustment. Medical knowledge was measured through pre- and postintervention multiple-choice questions. Learners' confidence and attitude towards medical errors disclosure were surveyed pre- and postintervention with assistance of the Barriers to Error Disclosure Assessment tool, revised with the addition of several questions related to provider-provider disclosure. Results Fourteen medical students participated in this pilot curriculum. Statistical significance was demonstrated in medical knowledge (p = .01), peer-disclosure skills (p = .001), and confidence in medical error disclosure (p < .001). Although there was improvement in patient-disclosure skills, this did not reach statistical significance (p = .05). Discussion This curriculum addresses the need for designated training in medical error disclosure. Learners gained knowledge, skills, and confidence in medical error disclosure. We recommend this curriculum for medical students preparing for transition to residency.